A critical environmental justice framework for the illegal wildlife trade - Green, Aalayna R. (Frontiers in Conservation Science, 2025)
Rapidly, scholars and practitioners are recognizing the need for the radical incorporation of justice into conservation interventions. Critical environmental justice is an attractive avenue for integrating justice and wildlife crime prevention within the illegal wildlife trade. As coined by David Pellow, critical environmental justice delineates dynamics of inequality related to intersecting social categories, multi-scalarity, racial expendability, and state power. Within IWT, these pillars of critical environmental justice offer opportunities to contend with futures otherwise and to pursue IWT intervention with a grounded understanding of communities, wildlife, and each other. This article demystifies the critical EJ literature and analyzes IWT through a critical EJ lens. Grounding IWT prevention and study in a critical EJ approach can facilitate a more seamless, radical, and transformative integration of justice principles into IWT intervention.